Immunological studies on the settlement-inducing protein complex (SIPC) of the barnacle Balanus amphitrite and its possible involvement in larva-larva interactions. - Matsumura, K (1998)
Immunological investigation has revealed that a settlement-inducing protein complex (SIPC), which induces cypris settlement of the barnacle Balanus amphitrite, is synthesized during larval development and accumulates in the cypris larva. We previously purified the SIPC from adult B. amphitrite, which was active when bound to a substratum. The SIPC is a glycoprotein of high molecular mass, consisting of three major subunits of 76, 88 and 98 kDa with lentil lectin (LCA)-binding sugar chains. In the present study, we prepared antiserum against each LCA-binding subunit of SIPC, and performed immunoblot analyses. Immunoblotting of adult extracts showed that anti-76-kDa antibody reacted only with the 76-kDa protein, whereas anti-88-kDa and anti-98-kDa antibodies reacted with both the 88-kDa and the 98-kDa proteins. Immunoblotting of larval extracts indicated that reactivity of the 76-kDa protein to anti-76-kDa antiserum increased during larval development and cyprid extracts reacted strongly. Moreover, by using immunostaining we found that the SIPC was contained in 'footprints' of cyprids, which have been shown to act as a settlement-inducing pheromone, and is secreted onto the antennular attachment discs. The results suggest that the SIPC (or SIPC-like proteins) is involved in both adult-larva and larva-larva interactions during settlement of the barnacle B. amphitrite.